2004
DOI: 10.1177/030089160409000219
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-Carboplatin Induced Radiation Recall Colitis

Abstract: Some chemotherapeutic agents can "recall" the irradiated volumes by skin or pulmonary reactions in cancer patients who previously received radiation therapy. We report a recall colitis following the administration of paclitaxel-containing regimen in a patient who had been irradiated for a carcinoma of the uterine cervix. A 63-year-old woman underwent a Wertheim operation because of uterine cervix carcinoma. After 8 years of follow-up, a local recurrence was observed and she received curative external radiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…There have been several published cases of radiation recall dermatitis induced by paclitaxel, [23][24][25][26] and another report of paclitaxel and carboplatin-caused radiation recall colitis. [27] In that case, colitis-related symptoms started the day after administration of chemotherapy. In our case, the time interval between the end of radiotherapy and the beginning of chemotherapy was approximately 1 month, whereas radiation recall myositis developed 4 months after chemotherapy, which was not a significantly different trend from previous reports.…”
Section: Discussionmentioning
confidence: 93%
“…There have been several published cases of radiation recall dermatitis induced by paclitaxel, [23][24][25][26] and another report of paclitaxel and carboplatin-caused radiation recall colitis. [27] In that case, colitis-related symptoms started the day after administration of chemotherapy. In our case, the time interval between the end of radiotherapy and the beginning of chemotherapy was approximately 1 month, whereas radiation recall myositis developed 4 months after chemotherapy, which was not a significantly different trend from previous reports.…”
Section: Discussionmentioning
confidence: 93%
“…Kundak, et al published the case of a 63-year-old woman, previously irradiated for cervical cancer, who developed radiation colitis following the administration of paclitaxel and carboplatin for multiple lung metastases. She presented with diarrhea and rectal bleeding after the administration of each course of chemotherapy and was treated with supportive care every time [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the immediate onset of the reaction, the absence of the reaction in some cases that were rechallenged with the same drug, and the nonexistence of atrophy on the skin after the recovery of the lesion do not support these hypotheses. [23,36,37] dermatitis, pneumonitis, esophagitis Bleomycin [19] dermatitis Capecitabine [38,39] dermatitis, gastritis Cyclophosphamide [29] dermatitis, panniculitis, and myositis Cytarabine [40] supraglottitis Dacarbazine [41] dermatitis Docetaxel [18,42,55] dermatitis, mucositis Etoposide [20] dermatitis 5-Fluorouracil [43] dermatitis Gemcitabine [2,4,34,44] dermatitis, myositis, colitis, optic neuritis, brainstem radionecrosis, lymphangitis, pericardial effusion, and tamponade Hydroxyurea [5] erythema Idarubicin [45] vaginal necrosis Interferon alpha 2B [46] dermatitis Methotrexate [47] dermatitis Oxaliplatin [48] dermatitis Paclitaxel [33,49,50] colitis, dermatitis, and pneumonitis Simvastatin [15] dermatitis Tamoxifen [51] dermatitis Trimetrexate [52] dermatitis Tuberculosis medication dermatitis (isoniazid, rifampicin, pyrazinamide) [53] Vinblastine [54] dermatitis…”
Section: Stem Cell Insufficiency and Increased Sensitivitymentioning
confidence: 99%
“…Similarly, histopathological findings are also nonspecific for internal organs. Kundak et al [33] reported that histological examination of the biopsy material taken from rectum revealed microabscesses and severe inflammation of the mucosa and the lamina propria, which were suggestive of radiation colitis. In the case that was reported by Vogl et al [34], a tissue sample from the pericardial window showed fibrin mixed with rare inflammatory cells and no evidence of malignancy, and pericardial fluid showed only reactive mesothelial cells and mixed lymphocytes.…”
Section: Histopathological Featuresmentioning
confidence: 99%